Lease Financing and Profitability: Evidence from Nigerian Quoted Conglomerates - Atseye, Fidelis Anake; Mboto, Helen Walter; Lawal, Suleiman Gbenga (International Journal of Economics and Financial Issues, 2019)
The paper examined the causal relationship between lease financing and profitability of Nigerian quoted conglomerates for the period spanning 2012 – 2017. The study focused on 6 conglomerates that are quoted on the Nigerian Stock Exchange as at 2017. Data were collated from published accounts of the affected companies. Data were analysed using descriptive and pooled OLS multiple regression statistics. Unit Root Test was conducted using Augmented Dickey –Fuller.. Estimated panel results indicated a negative and insignificant impact of Fixed Assets Turnover (FAT) on Return on Assets (ROA), Lease Financing (LFN) had a positive and insignificant impact on ROA, and Debt Ratio (LTDR) had a negative and insignificant impact on ROA. Firm size was used to control possible problem of non-linearity and heteroscedasticity. Based on these findings, leasing option was recommended as one of the sources of debt financing to boost the capital of Nigerian conglomerates to enable them to absorb losses, multiply fixed assets and grow continuously, thus providing employment and income in terms of tax revenue, profits, dividends, and wages and salaries to households for national growth and development. Keywords: Lease Financing, Profitability, Quoted Conglomerates JEL Classifications: G3, G32 DOI: https://doi.org/10.32479/ijefi.8942